Sidik-Chaula Urethroplasty and the Manset Flap for Non-Glanular Hypospadias Repair - Sukasah, Chaula L; Supit, Laureen (Lingkar Studi Bedah Plastik Foundation, 2012)
Hypospadias present with a wide array of meatal position and curvature. Choosing an operative technique for the different types of hypospadias has been challenging and controversial among the plastic, urologic, and pediatric surgeons. Regardless of the selected techniques, primary hypospadias repair still frequently results in complications requiring further surgery, such as fistula, residual chordee, and stricture. Owing to its practicality, the single stage urethroplasties are more-popular and widely used at present. However, our experience found higher rates of postoperative complications with the one-stage procedure compared to the two-stage for repair of non-glanular hypospadia. This article details the operative techniques of the two-stage Sidik-Chaula urethroplasty, a technique that we have implemented in our institution over two decades. It is applicable for the primary repair of any distal, middle, and proximal hypospadias. We also introduce the Manset Flap, a simple modification to the first stage of urethroplasty, which ease neourethra creation in the second stage. However, due to prior insufficient medical recordkeeping, we are yet unable to produce a quantified rate of success and complications by utilizing this technique. A study is currently being done to produce the numbers.